The dawn of a new ERA?: Australian Library & Information Studies (LIS) researchers further ranking of LIS journals - Smith, Kerry (Australian Library & information Association (ALIA), 2011)
The Australian federal government’s Excellence in Research Australian (ERA) (Excellence in research (ERA), 2009) policy initiative has given Australian LIS researchers the opportunity to review their listings of preferred journal titles that will be a component of measured research activity in the new federal government funding regimes. The Australian research environment and university reliance on ranking meant that the importance of ranking journal titles could not be ignored. The ranking of journal titles as submitted to the Research Quality Framework (RQF) exercise in 2007-8, was reviewed in a tight timeframe with a collegial response to calls for feedback. The results are reported and the anomaly of the place of Australian LIS in the Field of Research (FoR) category as assigned by the Australian Bureau of Statistics is discussed, as is the potential relevance of this categorisation regarding the choice of journal titles by these members of the LIS discipline.